Comparison of Two Intracanal Irrigants’ Effect on Flare-Up in Necrotic Teeth - Zarei, Mina; Bidar, Maryam (Iranian Endodontic Journal, 2008)
INTRODUCTION: The aim of this study was to compare the efficacy of two irrigants on decreasing the pain and swelling at different times after treatment of necrotic pulp. MATERIALS AND METHODS: Fifty patients with single canal tooth and necrotic pulp were selected and divided into two groups, twenty-five in each. Rotary files were used for preparing the canals and 0.2% chlorhexidine gluconate and 2.5% sodium hypochlorite were used for irrigation of canals. Then canals were filled by lateral condensation technique. A questionnaire was given to patients asking for the level of their pain and swelling. The patients were followed for 48h. Visual Analogue Scale (VAS) was used for determination of pain degree. The scale with 4 levels was used for measurement of the intensity of swelling. The data were statistically analyzed using Mann-Witney and Kruskal-Wallis tests. RESULTS: The research showed no significant difference between irrigant solutions in decreasing the amount of pain and swelling after endodontic treatments. No significant relationship was detected between the incidence of pain with swelling, age, and sex. Flare-up in maxilla was more than mandible. CONCLUSION: According to results of this in vivo study it was concluded that efficacies of 0.2% chlorhexidine gluconate and 2.5% NaOCl are the same.